Determinants of a Digital Work System for Financing SMMEs in South Africa - Ndabeni-Abrahams, Tembisa (University of the Witwatersrand, Johannesburg, 2024)
The purpose of this qualitative study is to explore the determinants of the digital work system for the fintech or digital financing ecosystem for South Africa. In digital financing, there is an expectation that digitalization would make access to finance easier, yet this has not happened as expected in developing countries such as South Africa. Some reasons are related to policy and regulation that remains unclear in many countries constraining the development of fintech solutions and broadly, digital financing. Therefore, this study sought to address the following primary research question: what are the determinants of the digital financing system of South Africa? Three secondary research questions were then asked to help in addressing the primary research question. A case study approach using critical realism as the research paradigm. South Africa was used as a case study, with data being collected from SEDA and SEFA representatives, with additional secondary data collected from the Enterprise Supplier Development forum, a community-of-practice group of SMMES and other partners in the small business sector. Face-to-face interviews were conducted with additional document analysis. Work Systems Theory (WST) was used as the analytical framework for understanding the digital work system for the fintech system in South Africa. The results of the analysis allowed three conclusions to be stated as follows: Government and other stakeholders and relevant SOEs such as SEFA and SEDA should foster financial innovation while maintaining financial system integrity. A multi-collaborative process for policymakers to rethink established policies of Fintech to recognize that recent trends in digital transformation requires a fresh look at policies. Secondly, investments in both physical and digital infrastructure is essential to enable comprehensive strategic initiatives that support small business sector growth. Third, insights from the analysis and discussions emphasize the pivotal role of stakeholders in shaping the digital financing landscape. While sometimes there is ‘conflicts’ in service provision, the themes of external collaboration, financial product innovation and market expansion are important determinants for collaboration interactions among stakeholders in a digital financing system.
A research report submitted in partial fulfillment of the requirements for the degree of Master of Management in the field of Digital Business to the Faculty of Commerce, Law, and Management, Wits Business School, University of the Witwatersrand, Johannesburg, 2024
Keywords: Digital Work System; Digital Finance; Work Systems Theory; Socio-Technical Systems; Digital Transformation; UCTD; SDG-8: Decent work and economic growth